Delay-induced Synchronization on a Dynamical Network of Euler’s Beams Indirectly Interconnected via a Piezoelectric Semi-active Control - Feulefack, Stève Cloriant Mba; Nbendjo, Blaise Rom'eo Nana (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, the effect of delay on a network of indirectly coupled Euler’s beams is analyzed. The system consists of a number of hinged-hinged beams indirectly interconnected to piezoelectric patches in a parallel conformation. A stability analysis is provided in order to give the threshold values of the parameter space for the onset of unstable motion. It is found that the stable region is reduced as the time delay increases. Disturbance-induced by time-delay on the synchronization state and the strong amplitude reduction (SAR) state is also presented. It is conventionally known that delay induces instability in coupled systems, but we find here that this delay can also contribute to stabilize these systems by synchronizing them.